2015
DOI: 10.1007/s11999-014-4054-3
|View full text |Cite
|
Sign up to set email alerts
|

Is Intralesional Treatment of Giant Cell Tumor of the Distal Radius Comparable to Resection With Respect to Local Control and Functional Outcome?

Abstract: Background A giant cell tumor is a benign locally aggressive tumor commonly seen in the distal radius with reported recurrence rates higher than tumors at other sites. The dilemma for the treating surgeon is deciding whether intralesional treatment is adequate compared with resection of the primary tumor for oncologic and functional outcomes. More information would be helpful to guide shared decision-making. Questions/purposes We asked: (1) How will validated functional scores, ROM, and strength differ between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 38 publications
3
56
1
8
Order By: Relevance
“…and Chadha et al . reported one recurrence in 12 and 9 patients, respectively, and Murray and Schlafly reported a recurrence rate of 27.7% in 18 patients. Compared with this last result, our relatively lower recurrence rate is likely attributable to the relatively short duration of follow‐up: our mean follow‐up was 3.5 years, whereas that of Murray's was 7.1 years.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…and Chadha et al . reported one recurrence in 12 and 9 patients, respectively, and Murray and Schlafly reported a recurrence rate of 27.7% in 18 patients. Compared with this last result, our relatively lower recurrence rate is likely attributable to the relatively short duration of follow‐up: our mean follow‐up was 3.5 years, whereas that of Murray's was 7.1 years.…”
Section: Discussioncontrasting
confidence: 45%
“…Many techniques have been used to reconstruct the defects, including vascularized/non‐vascularized fibular grafts, osteoarticular allografts, partial/total wrist arthrodesis and custom‐made prostheses. Each technique has its own unique possible advantages and disadvantages, which has been thoroughly discussed and debated .…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggested that en bloc resection and reconstruction can be used as the standard initial treatment method for Campanacci's grade II and III GCT. Wysocki et al (12) suggested that curettage can be considered for the initial treatment for Campanacci's grade II and III GCT of the distal radius, since en bloc resection can be performed if tumor recurrence occurred. However, secondary surgery not only increases the expense of the patients, it also increases the risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have identified the distal radius and ulna as being particularly prone to recurrence. To date, the ideal treatment methods for GCTs of the distal ulna and radius remain controversial (10)(11)(12). En bloc resection of GCT provides lower rates of recurrences, which also sacrifices the joint, results in a major reconstruction, and the functional outcomes are questionable.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with Campanacci Grades I and II lesions, intralesional curettage and cementation is the most common treatment. However, there is a high risk of local recurrence after this treatment method for patients with moreaggressive (Grade III) GCTs [1,33]. En bloc resection of Campanacci Grade III tumors with reconstruction is associated with a lower risk of local recurrence than curettage for these aggressive lesions [6,9,32,34].…”
Section: Introductionmentioning
confidence: 99%